2013
DOI: 10.1038/mt.2012.232
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Regeneration Enhanced by Ectopic Expression of ROS-detoxifying Enzymes in Transplant Mice

Abstract: High levels of reactive oxygen species (ROS) can exhaust hematopoietic stem cells (HSCs). Thus, maintaining a low state of redox in HSCs by modulating ROS-detoxifying enzymes may augment the regeneration potential of HSCs. Our results show that basal expression of manganese superoxide dismutase (MnSOD) and catalase were at low levels in long-term and short-term repopulating HSCs, and administration of a MnSOD plasmid and lipofectin complex (MnSOD-PL) conferred radiation protection on irradiated recipient mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…9,30 In addition, ectopic expression of manganese superoxide dismutase and catalase in HSCs reduces IR-induced HSC injury. 39 However, the molecular mechanisms by which ROS mediates the induction of HSC senescence by IR were unknown. The results from our current study suggest that ROS may mediate IR-induced HSC senescence in a telomere-independent manner, because increased production of ROS by irradiated HSCs was not associated with telomere shortening in HSCs and their progeny, even though increased For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…9,30 In addition, ectopic expression of manganese superoxide dismutase and catalase in HSCs reduces IR-induced HSC injury. 39 However, the molecular mechanisms by which ROS mediates the induction of HSC senescence by IR were unknown. The results from our current study suggest that ROS may mediate IR-induced HSC senescence in a telomere-independent manner, because increased production of ROS by irradiated HSCs was not associated with telomere shortening in HSCs and their progeny, even though increased For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In our study, we observed that NOD/SCID mice have significantly higher levels of reactive oxygen species (ROS) in bone marrow (BM) cells than other commonly used mouse strains. Given the previous studies from our laboratory 5,6 and others [7][8][9] showing that excessive ROS impaired the function of HSCs and that antioxidants were able to overcome the exhaustion of mouse HSCs in transplant recipients, we hypothesized that poor engraftment of HSCs in NOD/SCID mice could be partially attributed to higher levels of ROS in NOD/SCID BM. We used the antioxidant N-acetyl-Lcysteine (NAC) to reduce ROS levels in the NOD/SCID BM and demonstrated significant enhancement of the human cell engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ectopic overexpression of CAT can protect a variety of tissues against oxidative stress-induced damage in animal models [19][20][21]. Furthermore, there is evidence indicating that CAT treatment may preserve hematopoietic stem cell (HSC) selfrenewal in long-term BM cultures [22].…”
mentioning
confidence: 99%